Theory and structure of port competition - Ng, K; Ng, Koi Yu Adolf (2006)
﻿ Global economic development has significantly increased the demand for container liner shipping which has led to its global restructuring. Under such a situation, hub-and-spoke liner shipping systems have become increasingly popular which cause more intense competition between major ports and thus transhipment traffic is perceived to play a more important role in deciding the competitive positions of ports. Although there was no shortage of studies investigating port competitiveness in the past decades, most of them had overlooked the necessity of theorising port competition while ignoring the importance of including less-readily quantifiable factors in the port competitiveness assessment process. Thus, a research gap clearly exists and through investigating the competitiveness of Antwerp, Bremerhaven, Felixstowe, Hamburg, Le Havre and Rotterdam acting as container transhipment hubs in North Europe, this thesis attempts to theorise port competition. Apart from providing a theoretical framework, Port Competitiveness Model, to future port research, this thesis also aims to identify the major factors affecting port attractiveness, to assess port choice behaviour, to investigate the current port competitiveness and to forecast their future prospects in the market. Research methodology involves various quantitative modelling techniques including generalized cost calculations (to assess port attractiveness), Multinomial Logit Model (to assess port choice behaviours of liners and the current competitive positions of ports) and Logistic Regression (to predict port competitiveness in the future), while data collection includes a questionnaire survey of major liners and various in-depth interviews with port and shipping experts in Europe. Findings indicate that money and time are not sufficient to explain the choices of liners and other less-quantifiable factors like geography, quality of services, values and perceptions, inertia, limitations of liners are also significant. Rotterdam is currently the overall market leader in the North European transhipment market but may be fragile in resisting challenges from competitors while Hamburg is a regional leader in the Scandinavia-Baltic market. On the other hand, Bremerhaven is currently an underachiever but possesses potential if it changes its current competitive strategies while Antwerp also possesses potential but faces different problems in its developments. For poor performing ports like Felixstowe and Le Havre, they need to improve significantly before they can really compete. Also, results suggest that ports should not only focus on expensive physical improvements (like infrastructure) but should also pay attention to software aspects in port operations e.g. management, marketing, etc. The key to achieve port competitiveness does not depend on port's administrative system but on how it executes the system and makes things work. In the foreseeable future, the author firmly believes that this thesis will become one of the theoretical 'pillars' in the theory of port competition.